An intelligent approach for improving feature reduction \ - Basma Mostafa Abdelghany; Mohamed Saleh; Mohammed Elbeltagy; Mohammed Hassan Rasmy (Cairo : Basma Mostafa Abdelghany, 2013)
The proliferation of `Big Data` [2] in real- world applications makes efficient data mining challenging to achieve . Big data involve problems with high dimensionality and a large number of instances that become difficult to process using traditional data mining tools . Consequently there's a growing need for improving existing dimenionality reduction techniques
Thesis (M.Sc.) - Cairo University - Faculty of Computers and Information - Department of Operation Research and Decision Support
Issued also as CD
Keywords: Ant colony optimization; Classification; Data mining